2023
DOI: 10.1021/acs.accounts.2c00723
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of GalNAc in Mucin-Type O-Glycosylation

Abstract: Conspectus N-Acetylgalactosamine (GalNAc)-type O-glycosylation is an essential posttranslational modification (PTM) that plays fundamental roles in biology. Malfunction of this PTM is exemplified by the presence of truncated O-glycans in cancer. For instance, the glycoprotein MUC1 is overexpressed in many tumor tissues and tends to carry simple oligosaccharides that allow for the presentation of different tumor-associated antigens, such as the Tn or sTn antigens (GalNAc-α-1-O-Thr/Ser and Neu5Acα2-6GalNAcα1-O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Targeting MUC1-C to inhibit the AKT-S6K1-elF4A pathway regulates TIGAR translation in colorectal cancer and inhibits the growth of colon cancer cells in vitro ( 104 ). Glycosylation of MUC1 depends on the biomolecules it recognizes, such as, for example, GalNAc transferase, visfatin lectin, antibodies and other glycosyltransferases ( 105 ), while a research found that anti MUC1 treatment can inhibit C1GALT1 at protein level ( 106 ). In other words, the impact of C1GALT1 on MUC1 glycosylation has a certain influence on the development of colorectal cancer, although the specific mechanism is not yet fully understood.…”
Section: C1galt1 In Colorectal Cancermentioning
confidence: 99%
“…Targeting MUC1-C to inhibit the AKT-S6K1-elF4A pathway regulates TIGAR translation in colorectal cancer and inhibits the growth of colon cancer cells in vitro ( 104 ). Glycosylation of MUC1 depends on the biomolecules it recognizes, such as, for example, GalNAc transferase, visfatin lectin, antibodies and other glycosyltransferases ( 105 ), while a research found that anti MUC1 treatment can inhibit C1GALT1 at protein level ( 106 ). In other words, the impact of C1GALT1 on MUC1 glycosylation has a certain influence on the development of colorectal cancer, although the specific mechanism is not yet fully understood.…”
Section: C1galt1 In Colorectal Cancermentioning
confidence: 99%
“…Although the scope of use is limited to the liver-like lipid molecules, it has the following advantages: 1) good safety, no need for steroid pretreatment; 2) subcutaneous administration could be performed, and patient compliance is better; 3) high delivery efficiency, only 2–5 mg/kg dose could play a role. Lipid coupling has the problem of endosome escape ( Sanz-Martinez et al, 2023 ). Lipid-coupled RNA could form a polymer similarly to low-density lipoprotein (LDL), which not only extends the cycle time but also binds to LDL receptors or other receptors to enter cells through endocytosis and improve delivery efficiency, which is more commonly coupled to cholesterol ( Khan et al, 2023 ).…”
Section: Current Strategies For Improving the Properties Of Nanotechn...mentioning
confidence: 99%
“…Again, this category lacks specificity and detection module. (3) Labeling of glycans by recognition, , metabolic glycoengineering, , or chemoenzymatic modification , to convert the glycan information into detectable signals for real-time in situ reporting of glycans in living systems. These labeling techniques can further enable glycan editing through the formation of natural glycosidic linkages and the integration of click chemistry, thereby revolutionizing the way we study the biological functions of glycans.…”
Section: Introductionmentioning
confidence: 99%